Endovascular Treatment and Angiographic Characteristics of Aneurysms at the Origin of the Anterior Choroidal Artery - Wang, Yiheng; Yu, Jinlu (Frontiers in Neurology, 2022)
Background: The information available about the variations and anatomy of the anterior choroidal artery (AchA) with aneurysm at the origin of the vessel and the outcomes of endovascular treatment (EVT) for AchA aneurysms is incomplete. Materials and methods: A retrospective study of 54 consecutive patients who were admitted to our hospital with a diagnosis of AchA aneurysm and treated with endovascular treatment (EVT) was performed. The variations and anatomy of the AchA and the outcomes of EVT for AchA aneurysms were analyzed. Result: The 54 patients were aged 35 to 82 years (mean age, 56.1±19.7 years) and included 32 females (59.3%, 32/54). Regarding AchA anatomy, 63.5% of AchAs had a typical S-shaped course. The diameter of the AchA origin averaged 0.8±0.3 mm. Of all the AchA aneurysms, 51.9% were ruptured. The diameter of AchA aneurysms averaged 4.1±2.4 mm. Moreover, 40.7% of 54 cases had multiple aneurysms. Endovascular treatment (EVT) was assisted with stenting for 25.9% of 54 AchA aneurysms. An immediate Modified Raymond-Roy Classification (MRRC) grade of I was obtained in 96.3% of AchA aneurysm cases. After EVT, the ischemic complication rate was 13%. In total, 83% of patients had good outcomes, with a Glasgow Outcome Scale (GOS) score of 4-5. Follow-up angiography showed acceptable treatment results in this study. Conclusion: The study showed that the AchA had a complex angiographic anatomy in cases with aneurysms at the origin of the vessel and that the anatomical features can be helpful in EVT. EVT for aneurysms at the origin of the AchA had good outcomes.